2020
DOI: 10.1039/d0py00115e
|View full text |Cite
|
Sign up to set email alerts
|

Poly(p-phenylene)s tethered with oligo(ethylene oxide): synthesis by Yamamoto polymerization and properties as solid polymer electrolytes

Abstract: rsc.li/polymers Poly( p-phenylene)s tethered with oligo(ethylene oxide): synthesis by Yamamoto polymerization and properties as solid polymer electrolytes † Hannes Nederstedt and Patric Jannasch * Salt-containing supramolecular assemblies of rigid-rod polymers tethered with flexible ion-solvating side chains represent a synthetic pathway towards thin ion-conducting solid electrolyte membranes with high dimensional stability. In the present work we have synthesized poly( p-phenylene)s (PpPs) carrying di-, trian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…To circumvent this strategies of blending, copolymerization, and addition of traditional liquid battery solvents, such as propylene carbonate (PC), have been applied. [8,16,18,19] For example Nederstedt et al [20,21] prepared an LiPSTFSI-PEO block copolymer SICs and reached ionic conductivities of 10 -4 -10 -7 S cm -1 at 80 °C; Ma et al [10] obtained ≈10 -4 S cm -1 at 90 °C for an LiPSTFSI/PEO blend; Feng et al [17] created an LiPSTFSI-based copolymer reaching 10 -4 S cm -1 at 90 °C; and Bouchet et al [22] prepared an LiP-STFSI/PEO tri-block copolymer with >10 -5 S cm -1 at 60 °C. Beaudoin et al [23] also prepared an LiPSTFSI-PEO-LiPSTFSI tri-block copolymer with >10 -5 S cm -1 at 60 °C.…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent this strategies of blending, copolymerization, and addition of traditional liquid battery solvents, such as propylene carbonate (PC), have been applied. [8,16,18,19] For example Nederstedt et al [20,21] prepared an LiPSTFSI-PEO block copolymer SICs and reached ionic conductivities of 10 -4 -10 -7 S cm -1 at 80 °C; Ma et al [10] obtained ≈10 -4 S cm -1 at 90 °C for an LiPSTFSI/PEO blend; Feng et al [17] created an LiPSTFSI-based copolymer reaching 10 -4 S cm -1 at 90 °C; and Bouchet et al [22] prepared an LiP-STFSI/PEO tri-block copolymer with >10 -5 S cm -1 at 60 °C. Beaudoin et al [23] also prepared an LiPSTFSI-PEO-LiPSTFSI tri-block copolymer with >10 -5 S cm -1 at 60 °C.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of p PCl 2 -EO 4 is described in detail elsewhere . In brief, the synthesis began with tosylation of tetra­(ethylene glycol) monomethyl ether using sodium hydroxide as a base in a two-phase system of water and THF.…”
Section: Methodsmentioning
confidence: 99%
“…The polymerization was carried out by following a modified, previously reported method (Scheme c) . The copolymers were designated as P X where X refers to the molar ratio between EO and Li + ions in the product.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic analysis of the effect of polymer architecture on the conductivity revealed that the macromonomer and BASPs with equivalent Li salt loading had comparable ability of dissociating Li salts. Recently, a Yamamoto homocoupling reaction has been exploited to polymerize 2,5-dichlorophenolic monomers functionalized with short PEO chains [108] . The self-assembly of p -phenylene backbones resulted in stacked structures with phase separated soft EO domains, and their morphology was preserved upon addition of Li salt.…”
Section: Peo-based Solid Electrolytesmentioning
confidence: 99%